2019
DOI: 10.3389/fphys.2019.00637
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of New Onset Diabetes Mellitus Secondary to Acute Pancreatitis: A Systematic Review and Meta-Analysis

Abstract: Background and Aims: Patients who have an episode of acute pancreatitis (AP) frequently develop diabetes mellitus (DM) over time. The reported incidence of DM after AP varies depending on the severity, etiology and the extent of pancreatic necrosis during AP. We performed a systematic review to determine the incidence of new-onset DM after AP episode (s), and compared the rate of DM in AP patients based upon different disease characteristics. Methods: A total of 31 relevant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 73 publications
(146 reference statements)
9
82
0
7
Order By: Relevance
“…This, and other data, suggests that the theory of greater islet cell loss, leads to greater risk of developing T3cDM and impaired glucose metabolism. This has been supported by several studies [ 16 , 18 , 21 23 ]. Of note, some of these studies have predominantly severe cases, while others have a majority of mild cases, and often direct cohort comparison was difficult.…”
Section: Predictors Of Diabetes Of the Exocrine Pancreassupporting
confidence: 77%
See 4 more Smart Citations
“…This, and other data, suggests that the theory of greater islet cell loss, leads to greater risk of developing T3cDM and impaired glucose metabolism. This has been supported by several studies [ 16 , 18 , 21 23 ]. Of note, some of these studies have predominantly severe cases, while others have a majority of mild cases, and often direct cohort comparison was difficult.…”
Section: Predictors Of Diabetes Of the Exocrine Pancreassupporting
confidence: 77%
“…Another meta-analysis conducted in 2019 showed a similar pooled incidence of 23% [ 18 ]. Upon further sub-analysis, the investigators found the pooled incidence within 5 years was 20% and after 5 years was 37%, showing a trend for increased development of endocrine dysfunction over time.…”
Section: Incidence/prevalencementioning
confidence: 99%
See 3 more Smart Citations